Image Based Modelling of of Microstructural Heterogeneity in LiFePO4 Electrodes for Li-ion Batteries - Cooper,SJ; Eastwood,DS; Gelb,J; Damblanc,G; Brett,DJL; Bradley,RS; Withers,PJ; Lee,PD; Marquis,AJ; Brandon,NP; Shearing,PR (Journal of Power Sources, 2013)
Battery and fuel cell simulations commonly assume that electrodes are macro-homogeneous and isotropic. These simulations have been used to successfully model performance, but give little insight into predicting failure. In Li-ion battery electrodes, it is understood that local tortuosity impacts charging rates, which may cause increased degradation. This report describes a novel approach to quantifying tortuosity based on a heat transfer analogy applied to X-ray microscopy data of a commercially available LiFePO4 electrode. This combination of X-ray imaging and image-based simulation reveals the microscopic performance of the electrode; notably, the tortuosity was observed to vary significantly depending on the direction considered, which suggests that tortuosity might best be quantified using vectors rather than scalars.